A Study on Students’ Ability in Identifying Types of Supporting Ideas in The Texts - Destina Kasriyati (Universitas Lancang Kuning, 2016)
This research is concerned about students’ ability in identifying types of supporting ideas of text (Example and Illustration, Reason, Facts Statistics, and Description). The aim of this research is to increase their knowledge about types of supporting detail so they are not only read a text but also know about types of supporting detail. This research used descriptive quantitative, the writer taken the data used test; the test consists of ten items. After analyzing the data, writer concluded that the English students at the fourth semester in identifying types of supporting ideas were categorized into good level. The writer found that there were some of students have low proficiency in identifying types of supporting detailsand most of students have a good proficiency.